Function and evolution of allelic variations of Sr13 conferring resistance to stem rust in tetraploid wheat (Triticum turgidum L.). (29th May 2021) - Gill, Baljeet K.; Klindworth, Daryl L.; Rouse, Matthew N.; Zhang, Jinglun; Zhang, Qijun; Sharma, Jyoti S.; Chu, Chenggen; Long, Yunming; Chao, Shiaoman; Olivera, Pablo D.; Friesen, Timothy L.; Zhong, Shaobin; et al.
SUMMARY: The resistance gene Sr13 is one of the most important genes in durum wheat for controlling stem rust caused by Puccinia graminis f. sp. tritici ( Pgt ). The Sr13 functional gene CNL13 has haplotypes R1, R2 and R3. The R1/R3 and R2 haplotypes were originally designated as alleles Sr13a and Sr13b, respectively. To detect additional Sr13 alleles, we developed Kompetitive allele specific PCR (KASP™) marker KASPSr13 and four semi‐thermal asymmetric reverse PCR markers, rwgsnp37–rwgsnp40, based on the CNL13 sequence. These markers were shown to detect R1, R2 and R3 haplotypes in a panel of diverse tetraploid wheat accessions. We also observed the presence of Sr13 in durum line CAT‐A1, although it lacked any of the known haplotypes. Sequence analysis revealed that CNL13 of CAT‐A1 differed from the susceptible haplotype S1 by a single nucleotide (C2200T) in the leucine‐rich repeat region and differed from the other three R haplotypes by one or two additional nucleotides, confirming that CAT‐A1 carries a new (R4) haplotype. Stem rust tests on the monogenic, transgenic and mutant lines showed that R1 differed from R3 in its susceptibility to races TCMJC and THTSC, whereas R4 differed from all other haplotypes for susceptibility to TTKSK, TPPKC and TCCJC. Based on these differences, we designate the R1, R3 and R4 haplotypes as alleles Sr13a, Sr13c and Sr13d, respectively. This study indicates that Sr13d may be the primitive functional allele originating from the S1 haplotype via a point mutation, with the other three R alleles probably being derived from Sr13d through one or two additional point mutations. Significance Statement: A new resistant haplotype (R4) of Sr13, designated as Sr13d, was identified in the genotype CAT‐A1, and based on sequencing studies this allele is hypothesized to be a primitive functional resistant allele of Sr13 . We established from extensive rust tests that haplotypes R1 and R3 should be separated, and R3 was designated Sr13c and determined to be preferable to Sr13a for breeding, while Sr13d was undesirable for breeding due to susceptibility to stem rust Ug99.